Towards Improving the Employability of Urban Planning Graduates in Algeria - Kadri Assia; Boudemagh Souad Sassi; Saighi Ouafa (Economics and Business)
The objective of this research is the assessment of the employment offers and the competency framework of the urban planner’s trade. The research is based on the results of a survey carried out with urban planning graduates, dealing with the acquired competencies during the university training, and on the documentary analysis of the Algerian framework of competencies of the urban planner with regard to its counterparts – the Operational Register of Trades/Professions and the Professional Office of Qualification of Urban Planners in France. The adopted approach follows these stages: the inventory of 422 trade sheets; their breakdown into indicators; the analysis of the requirements for job access; the comparison of the Algerian urban planner sheet with the French one; and the crossing of their competencies. The assessment demonstrates the inadequacy of the Algerian urban planner framework with its French counterpart; the disrespect of Bloom’s taxonomy and the rules of writing competencies; and the mismatch between the training offer and the employment offers. The results allow for the development of employment opportunities and improvement of the relevance of the framework competencies for urban planners in Algeria in view of a better employability of this trade and the concordance between training and employment.